2019
DOI: 10.1186/s12889-019-7483-9
|View full text |Cite
|
Sign up to set email alerts
|

A multi-country survey of public support for food policies to promote healthy diets: Findings from the International Food Policy Study

Abstract: Background: Poor diet is a significant contributor to the burden of global disease. There are numerous policies available to address poor diets; however, these policies often require public support to encourage policy action. The current study aimed to understand the level of public support for a range of food policies and the factors associated with policy support. Methods: An online survey measuring support for 13 food policies was completed by 19,857 adults in Australia, Canada, Mexico, the United Kingdom (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
72
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(82 citation statements)
references
References 42 publications
6
72
1
3
Order By: Relevance
“…Particularly, high support was for food policies of requiring restaurants and coffee shops to report calorie amounts in foods and beverages, reducing salt amount in bread, eliminating hydrogenated oil from food products, and preventing written misleading nutrition information on food products, and preventing food advertisements without permission. These ndings are consistent with similar studies in Australia, Canada, Mexico, the U.K., and the U.S.A., where people tend to support intrusive food polices, such as calorie menu labeling, food package warnings, and maximum salt levels for packaged products [19,23].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Particularly, high support was for food policies of requiring restaurants and coffee shops to report calorie amounts in foods and beverages, reducing salt amount in bread, eliminating hydrogenated oil from food products, and preventing written misleading nutrition information on food products, and preventing food advertisements without permission. These ndings are consistent with similar studies in Australia, Canada, Mexico, the U.K., and the U.S.A., where people tend to support intrusive food polices, such as calorie menu labeling, food package warnings, and maximum salt levels for packaged products [19,23].…”
Section: Discussionsupporting
confidence: 90%
“…For example, in a study by Julia et al found that older French adults were more likely to support a sugary drink tax [26], while a study by Curry et al found that young American adults were more supportive of such a tax [27]. In addition, a greater health consciousness among women supporting food policies had been reported previously [23,28]. In the current study, awareness and support for food policies generally were among middle class income male young adults who were employed.…”
Section: Discussionmentioning
confidence: 93%
“…Participants were particularly supportive of reformulation around reducing salt content in packaged foods. 26,28,35 Older participants, 26,28 females 28 and those with university qualifications 28 were more likely to support this policy. One study found no variables were associated with support for this policy.…”
Section: Regulating Product Reformulationmentioning
confidence: 98%
“…Attitudes towards reformulation of products to contain less of a certain 'negative' ingredient, for example, sugar, salt or saturated fat, was investigated as a policy option in four studies. This policy initiative had moderate (60%) 28,35 to high (87%) 24 levels of support. Participants were particularly supportive of reformulation around reducing salt content in packaged foods.…”
Section: Regulating Product Reformulationmentioning
confidence: 99%
“…In 2019, Kwon et al reported the results of a multi-country survey (Australia, Canada, Mexico, UK, USA) to assess public support for food policies promoting healthy diets [68]. They found that taxes on sugary drinks were supported by 30.0% in the USA to 53.8% in Mexico.…”
Section: Discussionmentioning
confidence: 99%